Preparation method of iron phthalocyanine organic photocatalyst in wastewater treatment photo-Fenton process
By preparing iron phthalocyanine supramolecular (Self-PcFe(III)) and applying it in the photo-Fenton catalytic system, the problems of low efficiency and high cost of existing photocatalysis and Fenton reaction in wastewater treatment have been solved, and the Efficient removal of a variety of pollutants provides an economical and convenient sewage treatment method.
Patent Information
- Application Number
- CN202411464026.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
AI Technical Summary
The existing photocatalytic and Fenton reactions have problems in sewage treatment, the production of large amounts of sludge, the low regeneration efficiency of heavy metals and incomplete H2O2 decomposition, resulting in high actual costs and limited treatment capacity in a coexistence environment of multiple pollutants.
The preparation method of iron phthalocyanine organic photocatalyst is adopted, by dissolving commercial iron phthalocyanine in concentrated sulfuric acid, performing ultrasonic treatment and then slowly adding it dropwise into deionized water. The solid product is separated by centrifugation, washed repeatedly and vacuum dried to finally form Iron phthalocyanine supramolecular (Self-PcFe(III)) with high redox properties is used to construct a photo-Fenton catalytic system under the system of ultraviolet light and hydrogen peroxide.
In the system of UV light and hydrogen peroxide, Self-PcFe(III) significantly improves the synergistic removal ability of phenol and hexavalent chromium, and also shows better removal of various pollutants (such as heavy metals, antibiotics and dyes) The effect is to provide an efficient, economical and convenient sewage treatment method.
Smart Images

Figure CN119346173A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts for wastewater treatment, in particular to a method for preparing an iron phthalocyanine organic photocatalyst in a photo-Fenton process for wastewater treatment. Background Art
[0002] The photo-Fenton process is a wastewater treatment technology that combines photocatalysis and Fenton reaction, and is mainly used to remove refractory organic pollutants in water. The process uses light to activate the catalyst and promote the production of strong oxidants (such as OH radicals), thereby improving the treatment efficiency.
[0003] Referring to the application number CN202410636713, an ozone catalyst used in the ozone process for sewage treatment is provided. The patent proposes the following content: The present invention is applicable to the technical field of ozone process for sewage treatment, and provides an ozone catalyst used in the ozone process for sewage treatment, comprising the following components: nano-alumina, nano-titanium dioxide, nano-silicon dioxide, metal porphyrin compounds, metal phthalocyanine compounds, ammonium oxalate, strontium chloride, and diatomaceous earth; preferably, the components and their contents are as follows, in parts by mass: 24 to 36 parts of nano-alumina, 18 to 27 parts of nano-titanium dioxide, 12 to 18 parts of nano-silicon dioxide, 9 to 15 parts of metal porphyrin compounds, 9 to 15 parts of metal phthalocyanine compounds, 3 to 6 parts of ammonium oxalate, 2 to 7 parts of strontium chloride, and 32 to 54 parts of diatomaceous earth. The present invention adds metal porphyrin compounds and metal phthalocyanine compounds, and mixes them with nano-alumina, nano-titanium dioxide, nano-silicon dioxide, etc. in a specific proportion, and the mutual cooperation can greatly improve the ozone oxidation efficiency of the ozone catalyst;
[0004] Refer to the patent application number CN202410552366.3 for a method for preparing a self-supporting two-dimensional metal-organic framework array. The patent proposes the following content: This patent mainly addresses the problem that the current two-dimensional metal-organic framework (MOFs) as photocatalysts are easy to aggregate and difficult to recycle. A bimetallic two-dimensional TCPPMOFs (CF@Cu, Zn-TCPP) array structure was grown on a foam copper (CF) substrate by a heteroepitaxial growth method. The agglomeration of two-dimensional TCPP MOFs is avoided, and its large surface area and porous structure have good adsorption capacity for organic pollutants with different charged properties. Secondly, CF@Cu, Zn-TCPP has a narrow band gap (1.62eV), and its ordered ultrathin nanosheet array and Cu2+ / Zn2+ bimetallic structure promote the separation and transfer of charges, improve the light utilization rate, and achieve the synergistic effect between adsorption and photo-Fenton-like catalytic degradation functions.
[0005] The integrated structure of Cu / Zn-TCPP uniformly fixed on CF achieves efficient and simple recycling, and is expected to become an environmentally friendly and economical sewage treatment solution. This invention will provide new ideas for the rational design of two-dimensional photo-Fenton catalysts based on MOFs, thereby opening up new ways for the efficient removal of organic pollutants.
[0006] When implementing the existing technology, the following technical problems are found:
[0007] The existing research on photocatalytic wastewater treatment is mostly focused on the treatment of a single pollutant: oxidation of some organic matter or reduction of a heavy metal alone.
[0008] At the same time, in the traditional Fenton reaction The conversion rate is low, a large amount of iron-containing sludge is produced, and the regeneration of Fe 2+ The low efficiency and incomplete decomposition of H2O2 limit its large-scale application in wastewater treatment. Therefore, in order to overcome the shortcomings of photocatalysis and Fenton reaction, the two are synergistically improved to form a new photo-Fenton catalytic technology, which is a pollutant control method with great application prospects. However, the actual cost of photo-Fenton technology for treating sewage is relatively high, and its ability to treat pollutants in water environments where multiple pollutants coexist is limited.
[0009] Therefore, a new solution to the above problems needs to be proposed. Summary of the invention
[0010] The purpose of the present invention is to provide a method for preparing an iron phthalocyanine organic photocatalyst in a photo-Fenton process for wastewater treatment, so as to solve the technical problems raised in the background technology.
[0011] To achieve the above object, the present invention provides the following technical solution: a method for preparing an organic photocatalyst of iron phthalocyanine in a photo-Fenton process for wastewater treatment, comprising at least the following steps:
[0012] S1: dissolving commercial iron phthalocyanine in concentrated sulfuric acid and mixing to obtain a mixed solution;
[0013] S2: The solution is then subjected to ultrasonic treatment until the iron phthalocyanine is completely dissolved in concentrated sulfuric acid;
[0014] S3: slowly drop the iron phthalocyanine concentrated sulfuric acid mixed solution into deionized water;
[0015] S4: After the mixed solution is further stirred for a certain period of time, the solid product is separated by centrifugation and the supernatant is discarded;
[0016] S5: The obtained solid is repeatedly washed with deionized water until it becomes neutral, and then dried in an oven under continuous vacuum;
[0017] S6: The 1D PcFe(Ⅲ) nanomolecules obtained by exfoliation self-assemble in the solution through strong π-π interaction to form phthalocyanine iron supramolecular (Self-PcFe(Ⅲ)) H-aggregates with high redox properties.
[0018] Furthermore, the commercial iron phthalocyanine used in S1 is 30 mg to 50 mg, and the concentrated sulfuric acid used is 3 ml to 10 ml. The mixing temperature of the commercial iron phthalocyanine and the concentrated sulfuric acid in S1 is 25±2°C.
[0019] Furthermore, the ultrasonic treatment time of S2 is 10 minutes to 20 minutes.
[0020] Furthermore, the S3 is added dropwise into 90 ml to 110 ml of deionized water.
[0021] Furthermore, the certain time in S4 is 3 hours to 5 hours.
[0022] Furthermore, the temperature of the oven in S5 is 65-70° C., and the vacuum drying is continued for 6 hours to 9 hours.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention obtains Self-PcFe(III) by designing a preparation method. In an ultraviolet (UV, λ<365nm) hydrogen peroxide system, Self-PcFe(III) exhibits an enhanced synergistic removal ability of phenol-Cr(VI). By studying the UV light treatment effect of Self-PcFe(III) on heavy metals, antibiotics and dye pollutants, the results show that Self-PcFe(III) has a better removal effect on different pollutants (hexavalent chromium, organic phenol pollutant phenol, antibiotic sulfamethoxazole, laboratory dye Coomassie Brilliant Blue R250).
[0025] The present invention further adds hydrogen peroxide to the photocatalytic system to construct a photo-Fenton system. The results show that Self-PcFe(III) / ultraviolet light / hydrogen peroxide has a strong synergistic treatment ability for hexavalent chromium ions and phenol.
[0026] The present invention uses a single iron phthalocyanine supramolecule to carry out efficient photo-Fenton synergistic treatment of complex pollutants, which will provide a new method for treating livestock and poultry pollutants that is efficient, economical and convenient. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0028] Figure 1 This is a schematic diagram of the catalyst characterization combination of the present invention, wherein: Figure 1 (a) Schematic diagram of the synthesis route of Self-PcFe(Ⅲ); Figure 1 (b) XRD patterns of α-PcFe, β-PcFe, PcFe(II) and Self-PcFe(III); Figure 1 (c) FT-IR spectra of PcFe(II) and Self-PcFe(III);
[0029] Figure 2 Schematic diagram of the transmission electron microscope morphology and microstructure of Self-PcFe(III) of the present invention;
[0030] Figure 3 It is a schematic diagram of the treatment of different systems of the present invention in an environment where pollutants coexist; DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0032] Embodiment 1:
[0033] The preparation method of iron phthalocyanine organic photocatalyst in wastewater treatment photo-Fenton process comprises at least the following steps
[0034] S1: dissolving commercial iron phthalocyanine in concentrated sulfuric acid and mixing to obtain a mixed solution;
[0035] S2: The solution is then subjected to ultrasonic treatment until the iron phthalocyanine is completely dissolved in concentrated sulfuric acid;
[0036] S3: slowly drop the iron phthalocyanine concentrated sulfuric acid mixed solution into deionized water;
[0037] S4: After the mixed solution is further stirred for a certain period of time, the solid product is separated by centrifugation and the supernatant is discarded;
[0038] S5: The obtained solid is repeatedly washed with deionized water until it becomes neutral, and then dried in an oven under continuous vacuum;
[0039] S6: The 1D PcFe(Ⅲ) nanomolecules obtained by exfoliation self-assemble in the solution through strong π-π interaction to form phthalocyanine iron supramolecular (Self-PcFe(Ⅲ)) H-aggregates with high redox properties.
[0040] The commercial iron phthalocyanine used in S1 is 30 mg to 50 mg, and the concentrated sulfuric acid used is 3 ml to 10 ml. The mixing temperature of the commercial iron phthalocyanine and the concentrated sulfuric acid in S1 is 25±2°C.
[0041] The ultrasonic treatment time of S2 is 10 to 20 minutes.
[0042] In S3, the solution is added dropwise into 90 ml to 110 ml of deionized water.
[0043] The certain time in S4 is 3 to 5 hours.
[0044] The temperature of the oven in S5 is 65 to 70° C., and the vacuum drying is continued for 6 to 9 hours.
[0045] Embodiment 2:
[0046] Based on the above embodiment, this embodiment further proposes the following preferred solutions:
[0047] ① Dissolve 40 mg of iron phthalocyanine in 5 ml of concentrated sulfuric acid to form a mixed solution; ② Then, the solution was ultrasonically treated for 15 minutes and then slowly added to 100 ml of deionized water; ③ After the mixture was stirred for 4 hours, the solid product was separated by centrifugation and the supernatant was discarded; ④ The obtained solid was repeatedly washed with deionized water until neutral, and then vacuum dried in an oven at 65°C for 24 hours; ⑤ Subsequently, the peeled 1D PcFe(Ⅲ) nanomolecules self-assembled in the solution through strong π-π interaction to form iron phthalocyanine supramolecular (Self-PcFe(Ⅲ)) H-aggregates with high redox properties.
[0048] Based on the above two embodiments, this case proposes the following analysis process and results:
[0049] Catalyst characterization
[0050] like Figure 1 As shown in a, the synthesis route of Self-PcFe(Ⅲ) was proposed. The crystal structure of the material was analyzed by X-ray diffraction (XRD) technology ( Figure 1a). The XRD pattern reveals two crystal structures in PcFe(II): α-PcFe and β-PcFe. The diffraction peaks of α-PcFe appear at 6.8°, 7.4°, 10.4°, 16.4° and 26.1°, while the diffraction peaks of β-PcFe are located at 8.1°, 10.6°, 18.0°, 21.0° and in the range of 27.8-29.5°. This indicates that the PcFe(II) sample used contains both α-PcFe and β-PcFe crystal forms. Comparing the XRD patterns of PcFe(II) and Self-PcFe(Ⅲ), similar diffraction peaks are found at 6.9°, 9.3° and about 27°. This finding is consistent with previous literature reports and further verifies the successful synthesis of Self-PcFe(Ⅲ) and the characteristics of its crystal structure. It is worth noting that the characteristic peaks of β-PcFe do not appear in the XRD spectrum of Self-PcFe(Ⅲ), which indicates that during the concentrated sulfuric acid treatment and subsequent self-assembly process, the PcFe(II) of the β-PcFe crystal form may have been effectively removed, while the PcFe(II) of the α-PcFe crystal form was retained and self-assembled into the Self-PcFe(Ⅲ) organic semiconductor. In addition, the number of impurity peaks in Self-PcFe(Ⅲ) was significantly reduced, indicating that the concentrated sulfuric acid stripping and self-assembly process are effective in removing impurities in the material, improving the purity of Self-PcFe(Ⅲ) and making it better than the original PcFe(II). In the XRD spectrum analysis, no new diffraction peaks were observed, which means that during the self-assembly process of Self-PcFe(Ⅲ), the α-PcFe crystal form remained relatively stable and the structure did not change significantly.
[0051] Different chemical bonds have different vibration energies. When a sample absorbs infrared light of a specific wavelength, characteristic peaks related to the corresponding functional groups will appear in the infrared spectrum. To this end, we used Fourier transform infrared spectroscopy (FT-IR) analysis technology to characterize the functional groups of the material. Figure 1As shown in Figure b, in the wavenumber range of 800-4000 cm-1, we obtained rich chemical structure information of the material. Specifically, the absorption peak observed at 895 cm-1 is a typical characteristic peak of the N-Fe stretching vibration in iron phthalocyanine. In addition, the spectral bands at 1078 cm-1, 1120 cm-1 and 1163 cm-1 correspond to different vibration modes of the phthalocyanine benzene ring skeleton. The peaks at 1285 cm-1 and 1330 cm-1 represent the stretching vibration of the C=C double bond, while the peak at 1417 cm-1 belongs to the stretching vibration of the CN bond. It is worth noting that the broad peak at 1725 cm-1 may originate from the vibration of the C=N heterocycle, while the small peak at 3055 cm-1 is caused by the stretching vibration of the CH bond. More interestingly, in the FT-IR spectrum of Self-PcFe(Ⅲ), a small peak at 3120-3310cm-1 was found, which was not found in PcFe(II). This peak originates from the stretching and vibration of the chemical bonds containing the O element. Combining the FT-IR and XRD results, it can be concluded that the chemical structure of Self-PcFe(Ⅲ) after concentrated sulfuric acid stripping and self-assembly remains basically unchanged, retaining the skeleton vibration mode of PcFe(II).
[0052] The morphology and microstructure of Self-PcFe(Ⅲ) were characterized by transmission electron microscopy (TEM). Figure 2 ). CSA, as a strong acid, changes the surface charge distribution while dissolving PcFe(Ⅱ). This destroys the interactions between PcFe(Ⅱ) nanomolecules (such as van der Waals forces and electrostatic effects), causing the originally agglomerated PcFe(Ⅱ) to dissociate into single or smaller nanomolecular units. At the same time, the Fe(Ⅱ) in the phthalocyanine ring is oxidized to PcFe(Ⅲ) by the strong acid. TEM image ( Figure 2) revealed that Self-PcFe(Ⅲ) is a one-dimensional (1D) nanorod structure with a diameter ranging from 13.72nm to 23.52nm. This is due to the unique 18 π electron configuration and conjugated plane of Self-PcFe(Ⅲ) nanomolecules. During the self-assembly process, the π-π interaction between molecules prompts them to arrange and extend along the one-dimensional direction through regular face-to-face parallel stacking. At the same time during this extension process, the Self-PcFe(Ⅲ) nanomolecules produce stacks that move vertically along the phthalocyanine surface based on the Coulomb interaction between the chains. These two effects cause adjacent Self-PcFe(Ⅲ) molecules to overlap and eventually polymerize to form H-aggregates, which are displayed in the morphology of one-dimensional nanorods. The nanorods with a diameter of 23.52nm were observed when the nanorods were stacked and aggregated. This unique H-aggregate structure not only has a high aspect ratio, providing a direct path for charge transfer, but also the arrangement between the one-dimensional nanorods constitutes a complex open network, increasing the surface reaction sites in contact with pollutants. In addition, this H-aggregate can effectively resist the mechanical stress and deformation caused by long-term illumination and chemical reactions, ensuring the stability of the material.
[0053] In order to further discuss the advantages of Self-PcFe(II) coupled with Fenton technology in treating pollutants, the effects of the photo-Fenton system and the photocatalytic system in treating pollutants were compared. The pH was adjusted to 3 before the photoreaction, and the H2O2 concentration was adjusted to 20mM at time 0 of the photoreaction. When Self-PcFe(II) treated Cr(VI) in the coexisting environment in the photo-Fenton system (Self-PcFe(II) / UV / H202) and the photocatalytic system (Self-PcFe(II) / UV), the removal rates were similar. H202 had the worst effect, removing only 8.25% of Cr(VI). In addition, the removal rate of Cr(VI) by UV / H202 was 44.58%. Therefore, the pseudo-first-order reaction kinetic model was selected to compare the chemical reaction rates of each system. The k value of Self-PcFe(II) / UV / H202 was the highest, which was 0.1572min -1 , is Self-PcFe(II) / UV(0.515min -1 ) is 3.05 times, UV / H202(0.120min -1 ) is 13.1 times, H202(0.0073min -1). In addition, since Self-PcFe(II) / UV / H202 and UV / H202 both degraded all phenol within 20 minutes, the k value of the first 10 minutes of the reaction was calculated to compare the phenol treatment capabilities of each system. Self-PcFe(II) / UV / H202 degraded about 95% of phenol in 10 minutes. Within 10 minutes, the k value of Self-PcFe(II) / UV / H202 for treating phenol (0.3769min -1 ) is Self-PcFe(II) / UV(0.0237min -1 ) is 15.9 times, UV / H202(0.2001min -1 ) is 1.88 times, H202(0.0207min -1 ) is 13.96 times.
[0054] Figure 3 K values of different systems for treating (a) Cr(VI) and (b) phenol in an environment where pollutants coexist (the inset shows the Cr(VI) removal rate and phenol degradation curve).
[0055] In summary:
[0056] The present invention adopts a simple concentrated sulfuric acid stripping method for the first time to modify PcFe(II) and obtain Self-PcFe(III) organic supramolecular.
[0057] Self-PcFe(Ⅲ) supramolecules exhibit excellent oxidation performance under ultraviolet light, and can synergistically oxidize organic pollutants and reduce heavy metals to remove both simultaneously.
[0058] When hydrogen peroxide is added to the Self-PcFe(Ⅲ) supramolecule under ultraviolet light irradiation, a photo-Fenton system (Self-PcFe(Ⅲ) / UV / H2O2) is constructed, which has a better removal effect on pollutants and a removal rate much higher than photocatalysis.
[0059] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing an organic photocatalyst of iron phthalocyanine in a photo-Fenton process for wastewater treatment, characterized in that: At least the following steps are included S1: dissolving commercial iron phthalocyanine in concentrated sulfuric acid and mixing to obtain a mixed solution; S2: The solution is then subjected to ultrasonic treatment until the iron phthalocyanine is completely dissolved in concentrated sulfuric acid; S3: slowly drop the iron phthalocyanine concentrated sulfuric acid mixed solution into deionized water; S4: After the mixed solution is further stirred for a certain period of time, the solid product is separated by centrifugation and the supernatant is discarded; S5: The obtained solid is repeatedly washed with deionized water until it becomes neutral, and then dried in an oven under continuous vacuum; S6: The 1D PcFe(Ⅲ) nanomolecules obtained by exfoliation self-assemble in the solution through strong π-π interaction to form phthalocyanine iron supramolecular (Self-PcFe(Ⅲ)) H-aggregates with high redox properties.
2. The method for preparing the iron phthalocyanine organic photocatalyst in the wastewater treatment photo-Fenton process according to claim 1, characterized in that: The commercial iron phthalocyanine used in S1 is 30 mg to 50 mg, and the concentrated sulfuric acid used is 3 ml to 10 ml. The mixing temperature of the commercial iron phthalocyanine and the concentrated sulfuric acid in S1 is 25±2°C.
3. The method for preparing the iron phthalocyanine organic photocatalyst in the wastewater treatment photo-Fenton process according to claim 1, characterized in that: The ultrasonic treatment time of S2 is 10 minutes to 20 minutes.
4. The method for preparing the iron phthalocyanine organic photocatalyst in the wastewater treatment photo-Fenton process according to claim 1, characterized in that: The S3 is added dropwise into 90 ml to 110 ml of deionized water.
5. The method for preparing the iron phthalocyanine organic photocatalyst in the wastewater treatment photo-Fenton process according to claim 1, characterized in that: The certain time in S4 is 3 to 5 hours.
6. The method for preparing the iron phthalocyanine organic photocatalyst in the wastewater treatment photo-Fenton process according to claim 1, characterized in that: The temperature of the oven in S5 is 65-70° C., and the vacuum drying time is 6-9 hours.
Citation Information
Patent Citations
Ozone catalyst applied to sewage treatment ozone process
CN118558372A
Preparation method of self-supporting two-dimensional metal-organic framework array
CN118577305A